GxG epistasis in growth and condition and the maintenance of genetic polymorphism in Gambusia holbrooki. (29th April 2018) - Culumber, Zachary W.; Kraft, Brittany; Lemakos, Valerie; Hoffner, Erika; Travis, Joseph; Hughes, Kimberly A.
Abstract: Theory on indirect genetic effects (IGEs) indicates that variation in the genetic composition of social groups can generate GxG epistasis that may promote the evolution of stable polymorphisms. Using a livebearing fish with a genetic polymorphism in coloration and associated behavioral differences, we tested whether genotypes of social partners interacted with focal individual genotypes to influence growth and condition over 16 weeks of development. We found that IGEs had a significant influence on patterns of feeding, regardless of focal fish genotype. There was no influence of social environment on juvenile length, but there was significant GxG epistasis for body condition. Each focal juvenile was in better condition when its own genotype was not present in adult social partners. These data are consistent with negative frequency‐dependent selection in which each morph performs better when it is rare. Neither variation in feeding nor activity‐related behaviors explained variation in body condition, suggesting that GxG epistasis for condition was caused by physiological differences between the two genotypes. These findings indicate that GxG epistasis in a given polymorphism can generate fitness landscapes that contribute to the maintenance of that polymorphism and to maintenance of genetic variation for additional fitness‐related traits.